Gym usage behavior & desired digital interventions: An empirical study - RADHAKRISHNAN, Meeralakshmi (Institutional Knowledge at Singapore Management University, 2020)
Understanding individual’s exercise motives, participation patterns in a gym and reasons for dropout are essential for designing strategies to help gym-goers with long-term exercise adherence. In this work, we derive insights on various exercise-related behaviors of gymgoers, including evidence of a significant number of individuals exhibiting early dropout and also describing their attitudes towards digital technologies for sustained gym participation. By utilizing gym visitation data logs of 6513 individuals over a longitudinal period of 16 months in a campus gym, we show the retention and dropout rates of gym-goers. Our data indicates that 32% of the people quit their gym activity after initial 1 or 2 visits and about 65% ofthe users have less than 10 visits during the 16 months period. From this data, we also observed that people attending gym in a group and following a regular visiting time to the gym have a lower chance of ceasing gym activity. Further by surveying 615 individuals across varying demographics, we uncover the key reasons for dropout to be “lack of knowledge in using gym equipment" and “lack of access to a personal trainer", besides the prominent reason of “lack of time". Our survey also indicates the propensity of individuals towards using digital technologies (e.g., fitness apps) to track their gym activity. Somewhat surprisingly, our survey reveals a disinclination among individuals to use obtrusive wearable-based solutions in a gym, with 60% of them preferring a less-invasive and more convenient approach of machine-attached sensors for automated tracking of gym exercises.